Critical considerations on load-to-failure test for monolithic zirconia molar crowns. (November 2018) - Nakamura, Keisuke; Ankyu, Shuhei; Nilsson, Fritjof; Kanno, Taro; Niwano, Yoshimi; Vult von Steyern, Per; Örtengren, Ulf
Abstract: Application of monolithic zirconia crowns (MZCs) with reduced thickness to the molar region has been proposed, but potential complications have yet to be fully evaluated in laboratory tests. The present study aimed to develop a clinically relevant load-to-failure test in combination with fatigue treatments involving thermal and mechanical cycling (TC and MC) to evaluate the fracture resistance of molar MZCs. MZCs with a minimal thickness of 0.5 mm were bonded to dies made of resin-based composite (RBC), epoxy resin (EP), or polyoxymethylene-copolymer (POM-C). The samples were either untreated (UT) or subjected to TC (5–55 °C for 1 × 10 5 cycles) and MC (300 N for 2.4 × 10 6 cycles). The stress generated by TC and MC was simulated by finite element modeling. The load-to-failure test was performed using an inverse V-shaped two-plane indenter and was followed by fractographic analysis. The median values of fracture load for MZC/RBC and MZC/EP in the TC group were significantly lower than those in the UT group. MC also decreased the median value of fracture load for MZC/RBC significantly, but not that for MZC/EP and MZC/POM-C. Fractography revealed that the fracture started in the cervical area in all groups, which is similar to clinically failed crowns. The simulation confirmed stress concentration at the cervical area in both TC and MC groups. The present study suggests that the load-to-failure test using a two-plane indenter could induce clinically relevant fracture of MZCs, the vulnerability of the MZCs depends largely on the die material employed, and MZCs are more likely to be damaged by thermal fatigue than mechanical fatigue. Graphical abstract: Highlights: Load-to-failure test for zirconia crowns is performed using a two-plane indenter. The test results in crown fracture originating from a cervical area. Stress concentration in the cervical area is confirmed by finite element analysis. Vulnerability of the zirconia crowns largely depends on the properties of the die. The zirconia crowns are damaged by thermal fatigue more than mechanical fatigue.